The Role of Insulin-Like Growth Factor (IGF-1) Signaling During Physical Exercise: A Systematic Review - Novadri Ayubi; Junian Cahyanto Wibawa; Mohammed Aljunaid; Procopio B. Dafun Jr.; Jiang Wen Ming (مجله كليه طب الكندي)
Exercise is one of the non-pharmacological therapies that functions to improve public health. This study seeks to determine how increased IGF-1 levels during exercise as a hormone can trigger growth. For this study, a number of journal databases were searched, such as PubMed, Web of Science, Embase, and Science Direct. This study considers several aspects, such as research on exercise and IGF-1 published in reputable journals over the past five years. Our analysis only includes items published in reputable international journals. Using databases total of 159 publications were found. In this comprehensive analysis, about ten carefully selected and peer-reviewed papers were included. The standard operating procedure for this investigation was developed using Preferred Reporting Systematics and Meta-analysis (PRISMA). Based on the results of this systemic investigation, exercise has been shown to increase IGF-1 levels, a hormone that promotes growth. Physical exercise as a therapeutic effort and a means of improving public health.